Dietary copper and L-arginine: influence on pullet maturation and productivity - Hasan Rouhanipour; Omid Ashayerizadeh; Seyed Davood Sharifi; Behrouz Dastar (Journal of Applied Poultry Research)
Summary: In this study, different levels of copper and L-arginine (LA) were used in diets for pullets. The effects of these supplements were examined on sexual maturation parameters, blood biochemical profiles, immune system, and antibodies titer against Influenza A (H9N2-subtype), Newcastle (B1 Type), and infectious bronchitis virus (IBV) H120 vaccine strain during the rearing phase of pullets. A total of 360 Hy-Line W-80 white layer-type pullets (13-week-old) were used in two test periods: the first period (developer) from the age of 13-15 weeks, and the second period (pre-layer) from the age of 16-17 weeks. The pullets were assigned to a 2 × 3 factorial arrangement with two levels of supplemental Cu (15 and 30 mg/kg in the developer diet, denoted as Cu15, Cu30) and three levels of LA. These include the recommended level according to Hy-line (RHL), as well as 20% higher (LA20) and 40% higher (LA40) than the recommended level in the diet. The experiment was design a randomized complete block with 6 treatments. Each treatment had 6 replicates, with 10 birds per pen. The total duration of the experiment lasted for 6 weeks. Dietary inclusion of Cu15+LA40, Cu30+RHL, and as well as the use of diet supplemented with Cu30+LA20 increased shank length compared to the group fed Cu15+RHL in developer period (P<0.05). In pre-layer period, the birds fed with Cu15+LA40 diet had greater comb height than both Cu15+LA20 and Cu30+LA40 groups (P<0.05). Furthermore, birds fed with Cu30+LA20 diet exhibited lower levels of LDL and LDL/HDL ratio than those fed on the Cu15+RHL diet (P<0.05). Heterophile to lymphocyte ratio (HET/LYM) decreased in the birds fed with Cu15+LA40 and Cu30+LA20 compared to the Cu15+RHL treatment (P<0.05). Estradiol hormone increased in the blood serum of birds fed diets containing Cu30+LA20, compared to the Cu15+LA20 and Cu15+RHL diets (P<0.05). Based on the results, adding copper 15 and 30 mg copper/kg and L-arginine 40% higher than the recommended level to the growing phase diets of pullets have positive effects on performance parameters, blood biochemical profiles, and immune system. Also, physiological maturity indices improve within specific age ranges.